2009
DOI: 10.1016/j.socscimed.2009.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Demanding patient or demanding encounter?: A case study of a cancer clinic

Abstract: This paper explores the sociological relevance of demanding encounters between doctors and patients. Borrowing from Potter and McKinlay's (2005) reconceptualization of the doctor-patient relationship, we suggest an analytic shift away from `demanding patients' toward `demanding encounters'. Such a shift places provider-patient conflict within a broader sociocultural context, emphasizing constraints facing both doctor and patient as they interact in a clinical setting. Specifically, through an ethnographic stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 60 publications
0
37
0
Order By: Relevance
“…A final stream of research focuses on specific clinical trials and examines the perspectives of enrolled research participants (e.g., Bishop et al, 2012; Lowton, 2005; Morris & Balmer, 2006). Having some conceptual overlap with literature on pharmaceuticalization, this scholarship engages how research participants make sense of elements of study design (like randomization and placebo use) in ways that often underscore their desire for medical treatment, especially when their access to health care is limited (Stacey et al, 2009; Timmermans & McKay, 2009). …”
Section: Pharmaceuticalization and Drug Developmentmentioning
confidence: 99%
“…A final stream of research focuses on specific clinical trials and examines the perspectives of enrolled research participants (e.g., Bishop et al, 2012; Lowton, 2005; Morris & Balmer, 2006). Having some conceptual overlap with literature on pharmaceuticalization, this scholarship engages how research participants make sense of elements of study design (like randomization and placebo use) in ways that often underscore their desire for medical treatment, especially when their access to health care is limited (Stacey et al, 2009; Timmermans & McKay, 2009). …”
Section: Pharmaceuticalization and Drug Developmentmentioning
confidence: 99%
“…4 Examples outside of neurology include patients with viral upper respiratory symptoms who demand antibiotics, with chest pain from anxiety who demand a cardiac catheterization despite extensive negative noninvasive testing, or with fatigue who want a PET scan to look for cancer. These patients often see themselves as informed consumers who expect to receive requested interventions from their health care providers.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have found that some doctors enjoy the challenge of an IIP and are positive about the potential for greater patient education and involvement generated by the internet 6. Unfortunately, reports of negative reactions to IIP currently dominate, with the literature reporting doctors' reactions as frustration, irritation and even outright disgust.…”
Section: Definitionsmentioning
confidence: 99%
“…Researchers took a comprehensive observational approach in just two studies, interviewing patients preappointment and postappointment and also audio recording or observing the consultation 6 41. Most research was attitudinal and two prominent themes emerged from the attitudinal literature: the negative reactions reported by patients and doctors' justifications for such reactions.…”
Section: Patients' Use Of the Internet For Health Information And Thementioning
confidence: 99%